2D:4D digit ratio is not a biomarker of developmental programming in baboons (Papio hamadryas species). Issue 1 (16th October 2017) - Huber, Hillary F.; Li, Cun; Nathanielsz, Peter W.
Abstract: We hypothesized second‐to‐fourth hand digit ratio (2D:4D) is a biomarker of developmental programming in 3 baboon groups: intrauterine growth restriction (7 females, 8 males), exposure during fetal life to synthetic glucocorticoids (4 females, 5 males), and controls (66 females, 20 males). 2D:4D was similar between sexes and groups.